2000
DOI: 10.1002/(sici)1522-7243(200001/02)15:1<15::aid-bio570>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exhaustive exercise on human neutrophils in athletes

Abstract: The present study aims to investigate the effect of vitamin C intake following exhaustive aerobic training on Immunoglobulins A (IgA) and G (IgG) in a number of 24 wushu athletes. The study adopts an experimental design and a field study approach. The population of the study consisted of 62 wushu athletes in Oshnavieh County. From among the population, a number of 24 athletes were randomly selected as the participants and assigned into an experimental group taking vitamin C (N=12) or a control group without vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 32 publications
4
27
0
1
Order By: Relevance
“…Exercise also stimulates immune responses [69,70,72,73], with increased leucocyte numbers, in particular granulocytes, generated with bouts of moderate exercise. Exhaustive exercise in crosscountry skiers produced neutrophil mobilization and increased ROS generation on subsequent stimulation [72].…”
Section: Ros and Connective Tissuesmentioning
confidence: 98%
“…Exercise also stimulates immune responses [69,70,72,73], with increased leucocyte numbers, in particular granulocytes, generated with bouts of moderate exercise. Exhaustive exercise in crosscountry skiers produced neutrophil mobilization and increased ROS generation on subsequent stimulation [72].…”
Section: Ros and Connective Tissuesmentioning
confidence: 98%
“…In addition to their function in phagocytolysis and killing the pathological invaders, neutrophils have the ability to produce several mediators including LTB 4 [38,39], sICAM-1 [40] and IL-8 [41]. Although exercise has been shown to affect some of the neutrophils functions [42], it did not influence the release of LTB 4 , sICAM-1 and IL-8 by neutrophils stimulated with LPS in this study. We found that increased dietary fat intake (50% of calories) resulted in increased overall LTB 4 production and decreased post-exercise sICAM-1 production by neutrophils.…”
Section: Immunological Parameters In Vitromentioning
confidence: 99%
“…Several studies have shown that physical exercise promotes neutrophils activation through enzymatic activities such as MPO (Yamada et al 2000;Morozov et al 2003Morozov et al , 2006, which may lead into excessive ROS production. This enzyme is the main source for hypochlorous acid, which induces a transitory oxidative stress concomitant to the respiratory burst (Sureda et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…(Petersen et al 2001), activation of immunocompetent cell lines and neutrophil priming for acute phase response (Suzuki et al 1999). In addition, higher oxidized glutathione levels and lower antioxidant enzymes levels in neutrophils (Tauler et al 2002a), and the induction of acute phase proteins such as elastase or myeloperoxidase (MPO) are related to exhaustive exercise (Yamada et al 2000;Morozov et al 2003).…”
Section: Introductionmentioning
confidence: 99%